Dialysis modality-dependent changes in serum metabolites: accumulation of inosine and hypoxanthine in patients on haemodialysis - Choi, Ji-Young; Yoon, Yoo Jeong; Choi, Hee-Jeong; Park, Sun-Hee; Kim, Chan-Duck; Kim, In-San; Kwon, Tae-Hwan; Do, Jun-Young; Kim, Sung-Ho; Ryu, Do Hyun; Hwang, Geum-Sook; Kim, Yong-Lim (Nephrology, dialysis, transplantation, 2011)
The body metabolism of patients with end-stage renal disease may be altered in response to long-term dialysis treatment. Moreover, the pattern of serum metabolites could change depending on the type of dialysis modality used. However, dialysis modality-dependent changes in serum metabolites are poorly understood. Our aim was to profile comprehensively serum metabolites by exploiting a novel method of (1)H-NMR-based metabonomics and identify the differences in metabolite patterns in subjects receiving haemodialysis (HD) and peritoneal dialysis (PD). Anuric and non-diabetic HD patients were matched to PD patients for age, sex and dialysis duration. Accurate concentrations of serum metabolites were determined using the target-profiling procedure, and differences in the levels of metabolites were compared using multivariate analysis. Principal Components Analysis score plots showed that the metabolic patterns could be discriminated by dialysis modalities. Hypoxanthine and inosine were present only with HD, whereas serum xanthine oxidase activity and uric acid levels were not different. In contrast, PD was associated with higher levels of lactate, glucose, maltose, pyruvate, succinate, alanine, and glutamate linked to glucose metabolism and the tri-carboxylic acid cycle. Maltose appeared only in patients using icodextrin solution for PD. Known uraemic retention solutes such as urea, creatinine, myo-inositol and trimethylamine-N-oxide were increased in both dialysis groups. Metabonomics shows apparent differences in the profiles of serum metabolites between HD and PD, which were influenced by dialysis-related processes. Inosine and hypoxanthine are present only in HD patients, which is likely to represent more hypoxic and oxidative stress.